Prolonged Shedding of SARS-CoV-2 in Feces of COVID-19 Positive Patients: Trends in Genomic Variation in First and Second Wave - Lavania, Mallika; Joshi, Madhuri S.; Ranshing, Sujata S.; Potdar, Varsha A.; Shinde, Manohar; Chavan, Nutan; Jadhav, Santosh M.; Sarkale, Prasad; Mohandas, Sreelekshmy; Sawant, Pradeep M.; Tikute, Sanjaykumar; Padbidri, Vikram; et al. (Frontiers in Medicine, 2022)
The main route of transmission of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), are through respiratory pathways and close contact of person-to-person. While information about other modes of transmission is relatively less, some published literature supporting the possibility of a fecal-oral mode of transmission has been accumulating. SARS-COV-2 infected cases diagnosis is based on the real-time reverse transcription-polymerase chain reaction (RT-PCR). The fecal excretion of SARS-COV2 has been reported frequently however, the role of fecal viral load with severity of the disease is not yet clear. Our study focused on the investigation of SARS-CoV-2 shedding in the fecal samples of COVID-19 patients. A total of 280RT-PCR-confirmed patients were enrolled, 15.4% of whom had gastrointestinal symptoms. Sixty two percent of the patients showed positivity for SARS-CoV-2 RNA in fecal specimens. This positivity was not associated with the presence of gastrointestinal symptoms and the severity of illness. Next generation sequencing [NGS] of SARS-CoV-2 from fecal samples of patients was performed to analyze mutational variations. Findings from this study not only highlight the potential presence of SARS-CoV-2 in feces, but also its ongoing mutational changes and its potential role in fecal-oral transmission.